KAJIAN ONTOLOGIS LEMBAGA MEDIASI DI PENGADILAN - Rahadi Wasi Bintoro (Universitas Airlangga, 2016)
The implementation of mediation in court still seems formalistic. This condition makes the process of a civil case proceed to Supreme Court. Supreme Court Regulation No.1 of 2008 aimsto stream line the mediation institute incourt. However, in practice the Supreme Court Regulation No. 1 of 2008 was no different with Article 130 HIR, it even contrary to mediatio nontology and simple, fast and in expensive Justice Prinsiple. Mediation in court is institutionalization and empowerment of peace (court connected mediation) with the philosophical foundation is Pancasila which is the basis of our country especially the fourth precepts